Impact of entrepreneurial leadership on creative performance An Field study in a number of private colleges in the governorates of the Middle Euphrates - Ihsan Dahsh Jalab; Hamida Gheger Gremich (Iraqi Journal for Administrative Sciences, 2024)
The recent search aims to identify the entrepreneurial leadership influence represented by ( scenario enactment and cast enactment ) which concerned with administrative leadership of private colleges upon creative performance , to achieve the search objective , the private college has been selected in Central Euphrates governorates ( Najaf , Karbala , Dewhyania and Babylon ) . The search adopt related questioner as a tool to collect the necessary data to perform this search and achieve the sought objectives . 245 questioners were distributed , and (128) forms valid for analyzing obtained from the professors of private colleges mentioned above . The search used number of statistical methods , such as mean , standard deviation , and simple spherical correlation coefficient and simple linear regression coefficient . The results display there is significant positive correlation between leadership and creative performance . And there is also positive influence relation between entrepreneurial leadership and creative performance .